Chad Poverty Assessment : Investing in Rural Income Growth, Human Capital, and Resilience to Support Sustainable Poverty Reduction - World Bank (World Bank, Washington, DC, 2021)
This poverty assessment aims to inform poverty-focused policymaking in Chad. The report examines recent trends in poverty, inequality, and other social indicators and identifies key constraints on poverty reduction. Although agriculture, pastoralism, and related activities provide livelihoods for about 80 percent of the population, the capital-intensive oil sector drives macroeconomic growth, exports, and fiscal revenues. Eliminating poverty and boosting shared prosperity in Chad will require robust and sustained interventions along three strategic axes: (i) economic diversification, with a focus on the rural sector; (ii) building resilience to multidimensional shocks; and (iii) accelerating human capital formation. Chad faces enormous challenges, and the effectiveness of its poverty reduction efforts will hinge on factors that extend beyond economic policy, including the reestablishment of peace and security through improved governance, as well as a comprehensive effort to address the country’s profound gender disparities.